1991
DOI: 10.1172/jci115544
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chronic renal failure on Na,K-ATPase alpha 1 and alpha 2 mRNA transcription in rat skeletal muscle.

Abstract: Previous studies have suggested that an alteration in the expression of the NaK-ATPase of muscle may be an important determinant of enhanced insulin sensitivity in chronic renal failure. Therefore, in the present studies we have examined the effect of uremia on the NaK-ATPase a isoforms in skeletal muscle, at the level of mRNA expression and enzymatic activity. The activity of the sodium pump, as measured ouabain-sensitive 'Rb/K uptake in soleus muscle, revealed a reduction in the activity in uremia, related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
(19 reference statements)
1
18
0
2
Order By: Relevance
“…Somatostatin administration to fasting rats is followed by a greater increase in plasma potassium in uremic than in normal animals (48). Moreover, the ouabaininhibitable rubidium uptake by skeletal muscle from uremic rats is impaired (49). These observations in animals are in agreement with clinical studies, and show that fasting is followed by a rise in serum potassium in dialysis patients, but not in controls (50).…”
Section: Discussionsupporting
confidence: 63%
“…Somatostatin administration to fasting rats is followed by a greater increase in plasma potassium in uremic than in normal animals (48). Moreover, the ouabaininhibitable rubidium uptake by skeletal muscle from uremic rats is impaired (49). These observations in animals are in agreement with clinical studies, and show that fasting is followed by a rise in serum potassium in dialysis patients, but not in controls (50).…”
Section: Discussionsupporting
confidence: 63%
“…Da Silva et al (37) found significant decreases in cardiac mRNA for ␣2 without any changes in ␣2 protein observed. Bonilla et al (38) reported decreases in both Na ϩ /K ϩ ATPase activity as well as mRNA for the ␣1 isoform in skeletal muscle; however, these workers found an increase in ␣2 mRNA in this tissue. At present, the reason(s) for the discrepancy between our findings and these other studies is/are not clear.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, K ϩ adaptation seems to require an intact collecting duct, in particular a specific rise in Na ϩ , K ϩ -ATPase activity. 22 This is unrelated to aldosterone because the rise in Na ϩ , K ϩ -ATPase activity induced by K ϩ occurs in adrenalectomized animals. 23 Similarly, sheep on a high K ϩ intake achieve substantial increases in K ϩ excretion unrelated to either aldosterone or serum K ϩ .…”
Section: Discussionmentioning
confidence: 99%